1994
DOI: 10.1037/0021-9010.79.6.959
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a taxonomy of lateness behavior.

Abstract: Compared with other physical withdrawal behaviors such as employee turnover and absenteeism, employee lateness has been theoretically neglected. Three categories of lateness behavior (increasing chronic, stable periodic, and unavoidable) were denned on the basis of pattern, frequency, and duration of incidents. Hypothesized antecedents of each lateness category were tested using 2 samples, 353 hospital employees and 402 bank employees. Support was found for the idea that each category exhibits differential rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 49 publications
2
82
0
Order By: Relevance
“…This hypothesis is supported by Meyer et al (1993), who found that affective commitment was significantly negatively related to selfreported general tardiness. Several more studies have confirmed the relationship between commitment and lateness (Blau 1994;Blau et al 2004;Dishon-Berkovits and Koslowsky 2002;Foust et al 2006). As women's choices outside school are limited (Rosin and Korabik 1995), and as women in the teaching profession are able to cope more easily with the work-family conflict than other employed women, owing to their flexible hours and the short workday, it can be assumed that they are more committed to school than men and that the relationship between commitment and lateness will be stronger for them.…”
Section: Organizational Commitment Lateness and Gendermentioning
confidence: 90%
See 2 more Smart Citations
“…This hypothesis is supported by Meyer et al (1993), who found that affective commitment was significantly negatively related to selfreported general tardiness. Several more studies have confirmed the relationship between commitment and lateness (Blau 1994;Blau et al 2004;Dishon-Berkovits and Koslowsky 2002;Foust et al 2006). As women's choices outside school are limited (Rosin and Korabik 1995), and as women in the teaching profession are able to cope more easily with the work-family conflict than other employed women, owing to their flexible hours and the short workday, it can be assumed that they are more committed to school than men and that the relationship between commitment and lateness will be stronger for them.…”
Section: Organizational Commitment Lateness and Gendermentioning
confidence: 90%
“…Studies on gender and lateness indicate that women tend to be late more than men for demographic and occupational reasons (Barling et al 1994;Blau 1994;Gupta and Jenkis 1983;Hammer et al 2003). They usually ascribe this to the tendency for women to endure workfamily conflict more than men (Boyar et al 2005).…”
Section: Cross-cultural and Gender Differences In Latenessmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that they have a considerable voluntary component. Thus, in many cases, the nurses' ethical perspective plays a key role in explaining decisions to withdraw from work (Blau, 1994). Many established foundational theories, including equity theory (Adams, 1965), inducements-contributions theory (March and Simon, 1958), and social exchange theory (Thibault and Kelly, 1959) note the role of withdrawal behaviors as a means by which employees can withhold inputs from an organization.…”
Section: The Ethical Element In Withdrawal Behaviorsmentioning
confidence: 99%
“…The rationale for defining lateness as 6 min or more draws on hospital policy which defines lateness as arriving six or more minutes after the shift began and is supported by previous studies that indicated that this length of time is normatively unacceptable in various organizations (Blau, 1994(Blau, , 1995Blau et al, 2004). The data indicated 21.9 cumulative percent of 0-5 lateness frequency events; 15.8 cumulative percent of 7-13 lateness frequency events; and 13.7 cumulative percent of 14-39 lateness frequency events.…”
Section: Gendermentioning
confidence: 99%